2014
DOI: 10.4184/asj.2014.8.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Role of Coflex as an Adjunct to Decompression for Symptomatic Lumbar Spinal Stenosis

Abstract: Study DesignProspective cohort study.PurposeTo assess whether additional implantation of Coflex following spinal decompression provided better clinical outcomes compared to decompression alone for symptomatic lumbar spinal stenosis (LSS) and to determine whether improvement in clinical outcomes correlated with changes in the radiological indices studied.Overview of LiteratureLiterature on benefits of additional Coflex implantation compared to decompression alone for symptomatic LSS is limited.MethodsPatients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 30 publications
3
35
0
1
Order By: Relevance
“…However, Coflex group had the advantages of less trauma, less intraoperative blood loss, early ambulation and shorter hospitalization days compared with fusion group. The results of the present study were consistent with those of previous researches [21][22][23][36][37][38][39].…”
Section: Discussionsupporting
confidence: 93%
“…However, Coflex group had the advantages of less trauma, less intraoperative blood loss, early ambulation and shorter hospitalization days compared with fusion group. The results of the present study were consistent with those of previous researches [21][22][23][36][37][38][39].…”
Section: Discussionsupporting
confidence: 93%
“…Röder et al 19 noted significant benefit with coflex stabilization after decompression in a matched-pair cohort comparison study from the Swiss Spine Registry and the European Spine Tango database. Kumar et al 12 reported statistically significant improvement with open microsurgical decompression for spinal stenosis and statistically significant improvement when coflex ILS was added to the decompression. Furthermore, although not comparing the procedure with ILS, Budithi et al 2 demonstrated the importance of evaluating walking distance in patients with spinal stenosis undergoing decompression surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing ILS utilizing Coflex found greater clinical composite success (CCS), with no difference between adverse events compared to fusion patients, in a 48-month follow-up period. Another study found a significantly greater improvement in ODI score, as well as VAS back and leg pain scores, among Coflex patients compared to those receiving standard decompression alone [21]. Surgical complications among the Coflex group included one durotomy, while the decompression-only group experienced four durotomies and one surgical site infection.…”
Section: Next-generation Technologiesmentioning
confidence: 98%
“…Other studies have reported the maintenance of initially improved VAS up to 2 years [21, 27, 36•, 38] or even 3 years [13,23]. Of the latter studies, three are with next-generation products [23,27,38] and three correspond to last-generation [13,21,36•] IPDs. In the preparation of this manuscript, the authors could only find two RCTs in the literature comparing the success of pain reduction between next-vs. last-generation IPDs [23,33].…”
Section: Symptom Reliefmentioning
confidence: 99%